When the heart sings : [large type] a WWII women's fiction novel - Tolsma, Liz, 1966- (Music of hope series, 2019)
"The Nazis have forced Natia and Teodor from their Polish farm to a labor camp. Separated, Natia is chosen to be the housekeeper for the camp's overseer, and her husband Teodor is sent to work in the factory. Despite the strict camp rules--and the consequences for disobeying them--Natia finds a way to communicate with Teodor by sending messages through song as she passes Teodor's dormitory. But then Natia finds a Jewish orphan on the overseer's doorstep. She is determined to protect the boy and raise him as the child she and her husband were unable to bear--but if her German captors discover how much she's hiding, both she and Teodor may pay the ultimate price."--